Joint observation in NICU (JOIN): A randomized controlled trial testing an early, one-session intervention during preterm care to improve perceived maternal self-efficacy and other mental health outcomes. - Juliane Schneider; Mathilde Morisod Harari; Noémie Faure; Alain Lacroix; Ayala Borghini; Jean-François Tolsa; Antje Horsch; JOIN Research Consortium (PLoS ONE)
Background Parents of preterm infants in the Neonatal Intensive Care Unit (NICU) environment may experience psychological distress, decreased perceived self-efficacy, and/or difficulties in establishing an adaptive parent-infant relationship. Early developmental care interventions to support the parental role and infant development are essential and their impact can be assessed by an improvement of parental self-efficacy perception. The aims were to assess the effects of an early intervention provided in the NICU (the Joint Observation) on maternal perceived self-efficacy compared to controls (primary outcome) and to compare maternal mental health measures (perceived stress, anxiety, and depression), perception of the parent-infant relationship, and maternal responsiveness (secondary outcomes). Methods This study was a monocentric randomized controlled trial registered in clinicatrials.gov (NCT02736136), which aimed at testing a behavioural intervention compared with treatment-as-usual. Mothers of preterm neonates born 28 to 32 6/7 weeks gestation were randomly allocated to either the intervention or the control groups. Outcome measures consisted of self-report questionnaires completed by the mothers at 1 and 6 months after enrollment and assessing perceived self-efficacy, mental health, perception of the parent-infant relationship and responsiveness, as well as satisfaction with the intervention. Results No statistically significant group effects were observed for perceived maternal self-efficacy or the secondary outcomes. Over time, perceived maternal self-efficacy increased for mothers in both groups, while anxiety and depression symptoms decreased. High satisfaction with the intervention was reported. Conclusions The joint observation was not associated with improved perceived maternal self-efficacy or other mental health outcomes, but may constitute an additional supportive measure offered to parents in a vulnerable situation during the NICU stay.